Controllability and Observability Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Pontecchio (Bologna), Italy, July 1-9, 1968 - Evangelisti, E.; Evangelisti, E. (C.I.M.E. Summer Schools ;, 2011)
R.E. Kalman: Lectures on controllability and observability.- E. Kulikowski: Controllability and optimum contro.- A. Straszak: Supervisory controllabilityl.- L. Weiss: Lectures on controllability and observability.